Lattice Boltzmann study of fluid flow and heat transfer in random porous media - Liu, Minghua (2018)
In this thesis, the lattice Boltzmann (LB) method for transport phenomena is combined with the simulated annealing (SA) algorithm for digitized porous media reconstruction to study fluid flow and heat transfer in random porous media. It is noted that in contrast to previous studies which simplify porous media as arrays of regularly shaped objects or effective pore networks, the LB+SA method in this thesis can model statistically meaningful random porous structures in irregular morphology, and simulate pore-scale transport processes inside them. To be specific, this thesis applies the SA algorithm to construct digitized random porous structures based on limited but meaningful statistical morphological information, which is defined either by analytical formulas or experimental samples. Then the LB models are applied to simulate isothermal fluid flow, heat conduction and heat convection in these digitized representations. The results of simulations in this thesis demonstrate that the LB+SA numerical strategy can well resolve pore-scale fluid transport details in random geometries, which is far beyond the common simplifications of real porous media as arrays of regular-shape objects. More significantly, the upscaling averages over the computational volumes and the related effective transport properties were also computed based on these pore-scale numerical results. Good agreement between the numerical results and theoretical predictions or experimental data at REV-scale was found. Moreover, this multiscale approach reveals the intrinsic links between porous structure characteristics to pore-scale and REV-scale fluid transport features. It evidences how the irregular geometries impact the flow and heat transfer processes, and presents unusual phenomenon of occlusion in percolation which cannot be manifested in simplification of porous media as arrays of regular-shape objects. The numerical simulations in this thesis demonstrate a combination of the LB method with the SA algorithm is a viable and powerful numerical strategy for simulating transport phenomena in random porous media with complex geometries at pore-scale.